2007
DOI: 10.1007/s10734-005-1976-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic careers of immigrant women professors in the U.S.

Abstract: The article draws on the narratives of 34 immigrant women professors from 22 different countries who teach in a major research university in the U.S. First, the article presents immigrant women professors' voices of experiencing traditional academic activities in terms of teaching, research, and administration/service. Second, the paper voices women's stories of social climate prevailing in their departments and institutions that affects their academic careers. Third, the article narrates women's expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 20 publications
4
118
1
1
Order By: Relevance
“…For example, the finding that women faculty at NRU face challenges in balancing professional work and family life is not a new one (Acker 2003;Caplan 1993;Gaskell et al 2004;Gregory 2006;Probert 2005;Skachkova 2007). Balancing work and family obligations seemed particularly challenging during pregnancy and the early years of child rearing, but the demanding nature of Chinese schools and the intense competition for eventual seats at the university also appeared to extract a good deal of women's time in the capacity as evening and weekend tutor for their child.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the finding that women faculty at NRU face challenges in balancing professional work and family life is not a new one (Acker 2003;Caplan 1993;Gaskell et al 2004;Gregory 2006;Probert 2005;Skachkova 2007). Balancing work and family obligations seemed particularly challenging during pregnancy and the early years of child rearing, but the demanding nature of Chinese schools and the intense competition for eventual seats at the university also appeared to extract a good deal of women's time in the capacity as evening and weekend tutor for their child.…”
Section: Discussionmentioning
confidence: 99%
“…Research and writing in North America have consistently noted barriers women academics face in managing home and work responsibilities (Acker 2003;Caplan 1993;Skachkova 2007). For example, tension between career and family care among women faculty in Canada and the United States is captured by Caplan's (1993) work, who noted that a common dilemma many female faculty members face is whether to inform their departments about childcare or motherhood obligations.…”
Section: Women Academics and University Life From A Global Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Here, a number of mostly qualitative studies show that expatriate academics, at times, experience feelings of loneliness and isolation contributing to them being less satisfied on the job than their local counterparts (Lin et al, 2009). For example, Skachkova (2007) found that expatriate academics regularly experience exclusion based on collegial ethnocentrism. In a different study by Garson (2005), the author, an American expatriate, also described how she was informally excluded from a central network of colleagues at an Egyptian university.…”
Section: Literature Reviewmentioning
confidence: 96%
“…One of the issues often mentioned is the feeling of isolation and loneliness experienced by expatriate academics (Skachkova, 2007).…”
mentioning
confidence: 99%